Jeruso quiere ser gente - Mateos, Pilar; Ruano, Alfonso (Madrid : Ediciones SM, 2000)
Jeruso works as a bike messenger for a store. He dreams of directly working with the store's customers, but his boss refuses to let him. When getting ready to deliver a package to a customer, he notices that the package on his bicycle is gone. He suspects that some of the people from the neighborhood have stolen it. However, the people turn out to be nice and try to help him. Ultimately, Jeruso realizes that he had forgotten to pick up the package from the warehouse.
Premio El Barco de Vapor 1981.
Premio Lazarillo, 1982.
Keywords: Bicycle messengers -- Fiction